Identifikasi Tingkat Kepuasan Pengunjung Wisata Menggunakan Metode Naive Bayes - Fisyanda Yusmalizar; Yani Maulita; Suci Ramadani (Bulletin of Multi-Disciplinary Science and Applied Technology, 2023)
One way to implement development in all these fields is through development in the tourism sector, namely by developing and utilizing existing tourism resources and potential. To support government programs in developing tourist objects, especially in Bukit Lawang, it is necessary to pay attention to the level of satisfaction of tourist visitors visiting Bukit Lawang. To measure the level of satisfaction with tourist visitors, of course, parameters or assessment criteria will be used starting from road access to tourist attractions to cottage facilities. Measuring the level of satisfaction is usually done manually, namely by distributing or conducting surveys of visitors. If only questions are asked without any stored data, of course the Tourism Office will have difficulty measuring or evaluating the level of tourist visitor satisfaction, because it does not have sufficient data. For this reason, it is necessary to build a system that can assist the Langkat Regency Tourism Office in identifying the level of visitor satisfaction at Bukit Lawang. With this system, of course the Department will find it easier to evaluate and identify the level of visitor satisfaction quickly and precisely. So that all deficiencies to visitor satisfaction can be resolved quickly. To measure the level of satisfaction required a method that can measure the level of satisfaction precisely, one of the methods used is Naive Bayes. Naive Bayes is a simple probabilistic classifier that calculates a set of probabilities by summing the frequencies and combinations of values from a given dataset. Based on the results of trials that have been carried out in this study, results are obtained based on the 20 data used with the results of 17 TRUE data and 3 FALSE data, with an accuracy value of 65%.